REMEDIATION OF TEXTILE DYES MIXTURES USING TIO2/VIS PHOTOCATALYSIS AND FENTON FE2+/H2O2 - Andrade, P. M.; Carvalho, M. A. F.; Miranda, A. S.; Marques, H. R.; Campos, S. R.; Brito, N. N. Brito (Revista Brasileira de Engenharia de Biossistemas, 2015)
This study aimed to use the following treatment technology: TiO2 photocatalysis and Fenton reaction for the remediation of mixture of textile dyes. For the photocatalytic treatment it was obtained a reduction in color of 80% and Chemical Oxygen Demand of 60% using for this 600 mg L-1 of TiO2, 1500 mL min-1 recirculation flow, temperature 40 oC/45 oC and pH = 6.3 for 60 minutes of treatment. By Fenton reaction it was reached color reduction at 95% and Chemical Oxygen Demand reduction at 75% employing 60 mg L-1 H2O2, 50 mg L-1 de Fe2+ and pH = 4.0 for 62 minutes of treatment.